2012
DOI: 10.1007/s00068-012-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

Blind subxiphoid pericardiotomy to relieve critical acute hemopericardium: a final report

Abstract: BSP was safe and effective for cardiac tamponade due to acute hemopericardium. Critical complications during PCD for hemopericardium could not be avoided in some cases because of clots in the pericardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, pericardiocentesis and a subxiphoid pericardiotomy are often ineffective for cardiac decompression with clot formation within the pericardial space [3]. In our patient, adequate drainage and hemodynamic stabilization were not achieved with a subxiphoid pericardiotomy.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, pericardiocentesis and a subxiphoid pericardiotomy are often ineffective for cardiac decompression with clot formation within the pericardial space [3]. In our patient, adequate drainage and hemodynamic stabilization were not achieved with a subxiphoid pericardiotomy.…”
Section: Discussionmentioning
confidence: 58%
“…However, a prompt diagnosis and treatment can be lifesaving in cardiac tamponade [1], [2]. Although chronic cardiac tamponade is relieved using pericardiocentesis or a subxiphoid pericardiotomy in heart disease, these are often ineffective as cardiac decompression procedures with clot formation within the pericardial space in traumatic cases [3]. The typical physical findings of cardiac tamponade are not always apparent with life-threatening acute cardiac tamponade after blunt trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] Pericardiotomy in recent studies has been found to be superior to pericardiocentesis for a multitude of reasons, including decreased rates of failure to relieve pressure, decreased rates of complications such as damage to surrounding structures, and increased rates of survival. 7 In our patient, the use of point-of-care ultrasound was able to quickly make the diagnosis of cardiac tamponade and clotted blood in the pericardium. Knowing this information allowed this patient to undergo definitive management.…”
mentioning
confidence: 67%